2002
DOI: 10.1523/jneurosci.22-19-08574.2002
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Fibroblast Growth Factor 2 Promotes Oligodendroglial Repopulation of Demyelinated White Matter

Abstract: This study takes advantage of fibroblast growth factor 2 (FGF2) knock-out mice to determine the contribution of FGF2 to the regeneration of oligodendrocytes in the adult CNS. The role of FGF2 during spontaneous remyelination was examined using two complementary mouse models of experimental demyelination. The murine hepatitis virus strain A59 (MHV-A59) model produces focal areas of spinal cord demyelination with inflammation. The cuprizone neurotoxicant model causes extensive corpus callosum demyelination witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
180
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(201 citation statements)
references
References 70 publications
20
180
1
Order By: Relevance
“…Furthermore, pharmacological inhibition of notch signaling may enhance remyelination [9]. Our analysis of FGF2 null mice indicated improved remyelination associated with removal of FGF2 inhibition of OP differentiation, while we did not find evidence of an FGF2 effect on OP proliferation in vivo [2,3,15].…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Furthermore, pharmacological inhibition of notch signaling may enhance remyelination [9]. Our analysis of FGF2 null mice indicated improved remyelination associated with removal of FGF2 inhibition of OP differentiation, while we did not find evidence of an FGF2 effect on OP proliferation in vivo [2,3,15].…”
Section: Discussioncontrasting
confidence: 52%
“…Our work in FGF2 null mice demonstrated that FGF2 inhibits differentiation of oligodendrocyte progenitor (OP) cells into myelinating oligodendrocytes during both development and remyelination [3,14,15]. Importantly, FGF2 limits effective remyelination following chronic demyelination [2].…”
Section: Introductionmentioning
confidence: 95%
“…Areas of acute and chronic demyelination have increased expression of FGF2 ligand and FGF receptors [11,26,36,37]. In contrast with predictions from in vitro studies, OP proliferation in demyelinated lesions was not impaired in FGF2-null mice, indicating that the potential for FGF2 to act as an OP mitogen may not be a significant role of endogenous FGF2 in vivo during demyelination [37]. Studies testing elevated levels of FGF2 indicate a potential mitogenic role of FGF2 signaling, which may be distinct from the response elicited by endogenous FGF2 in lesioned white matter.…”
Section: Stimulating Proliferation To Counter Op Depletion In Chronicmentioning
confidence: 99%
“…With cuprizone demyelination of the corpus callosum, toxicity is primarily within mature oligodendrocytes, presumably because of the metabolic load of maintaining the extensive myelin membranes [39]. During cuprizone treatment, OP populations proliferate both within the demyelinated areas of white matter and in the adjacent SVZ [15,29,37]. By contrast, demyelination models of lysolecithin or ethidium bromide injection have significant loss of OP cells within lesion areas [40,41].…”
Section: Tapping Into Multiple Sources Of Op Cellsmentioning
confidence: 99%
“…56 FGF2 even stimulated post-mitotic oligodendrocytes to reenter the S-phase of the cell cycle, while FGF2 knockout enhanced OPCs differentiation and promoted oligodendrocyte repopulation in the demyelinated area following CPZ insult. 57,58 Moreover, activation of microglia by CPZ led to increased growth factor production and secretion of pro-inflammatory cytokines such as TNFa (tumor necrosis factor a) and IFNg(interferon-g). [3][4][5]59,60 The latter (IFN-g)was shown to inhibit cell cycle exit in oligodendrocyte progenitor cells and attenuate MBP expression.…”
Section: Flavopiridol Alleviated Cpz-induced Activation Of Astrocytesmentioning
confidence: 99%